Rancang Bangun Sistem Informasi Pengolahan Nilai Berbasis Website di SMK Ma’arif Terpadu Cicalengka - Fatiana N. Sahidah; Muhamad Fahmi Nugraha; Bayu Priatna; Kanda M. Ishak (Ma'soem University, 2023)
The design of the value processing information system is a system created to solve problems in the administration department at SMK Ma'arif Terpadu Cicalengka, more precisely in the student value processing section. The process of processing student grades data at SMK Ma'arif Terpadu Cicalengka is still manual in synchronizing grades from subject teachers with homeroom teachers, so it can cause problems, namely it can take a lot of time to synchronize, the ineffectiveness of processing student grades, and cannot be accessed by students as information. The purpose of this research is to build a website-based value processing application system which is expected to help simplify and shorten the time in processing grades at SMK Ma'arif Terpadu Cicalengka. This thesis is made based on the Object Oriented Analysis and Design (OOAD) method approach, which includes feasibility study, investigation, analysis, design, implementation, and review and maintenance. Then use the RUP (Rational Unified Process) method approach as a system development method that focuses on architecture (architecture-centric), and is more directed based on use cases (use case driven). The final result of research is the development of the Student Values Information System Design application at SMK Ma'arif Terpadu Cicalengka is the existence of a website-based application that can provide convenience in the processing of grades at SMK Ma'arif Terpadu Cicalengka.